2018
DOI: 10.1080/1343943x.2018.1543546
|View full text |Cite
|
Sign up to set email alerts
|

Towards the partial resumption of agriculture with buckwheat cultivation in fields physically decontaminated of radioactive cesium after the nuclear power plant accident in 2011: a case study in Yamakiya District, Fukushima

Abstract: Yamakiya District in the town of Kawamata, Fukushima Prefecture, was evacuated after the nuclear accident at the Tokyo Electric Power Company's Fukushima Dai-ichi nuclear power plant in 2011. Since then, nuclear decontamination procedures have been applied to the surrounding environment, including agricultural fields. The decontamination procedure for agricultural fields consists of the removal of radiation-contaminated surface soil, followed by soil dressing and plowing. However, radioactive cesium (RCs) rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The field used in this study could have had considerable variation in RCs concentration. However, the variation might have been reduced by tillage prior to cultivation 18 . Blanchet et al suggested that the distribution of available soil K forms in the upper soil layer (0-20 cm) is influenced by land uses, such as agricultural practices 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field used in this study could have had considerable variation in RCs concentration. However, the variation might have been reduced by tillage prior to cultivation 18 . Blanchet et al suggested that the distribution of available soil K forms in the upper soil layer (0-20 cm) is influenced by land uses, such as agricultural practices 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Challenges in resuming agriculture in areas in which evacuation orders have been lifted are in progress 18 . Increasing the understanding of RCs translocation from soil to crops is ongoing and important for the resumption of agricultural practices and the reconstruction of communities in these areas.…”
Section: Residual (Soilmentioning
confidence: 99%
See 1 more Smart Citation